Akulturasi Arsitektur Islam di Uzbekistan dan Kirgizstan: Kajian Historis-Kultural Warisan Jalur Sutra - Marsya Dwi Amailia (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2025)
This study aims to analyze the processes of architectural acculturation in Islamic architecture in Uzbekistan and Kyrgyzstan and to identify the forms of cultural interaction that have shaped its development. Situated along the historic Silk Road, both countries experienced intensive encounters between Islam and diverse cultural traditions, including Persian, Turkic, Mongol, Chinese, and indigenous nomadic cultures. The research employs a qualitative method with a historical-cultural approach and comparative analysis. Data were collected through an extensive literature review of scholarly publications, historical documents, and relevant sources on Islamic architecture in Central Asia. The data were subsequently analyzed through data reduction, classification, historical interpretation, and cross-case comparison. The findings reveal that architectural acculturation in Uzbekistan evolved into a monumental Persian-Timurid architectural tradition characterized by grand domes, iwans, blue ceramic mosaics, and intricate geometric ornamentation, as exemplified by architectural landmarks such as Registan and Shah-i-Zinda. In contrast, architectural acculturation in Kyrgyzstan demonstrates a greater degree of adaptation to nomadic cultural traditions through the use of local materials, functional building forms, and the incorporation of Chinese architectural elements alongside Turkic traditions, particularly evident in the Dungan Mosque in Karakol. The study further demonstrates that architectural acculturation in Central Asia constitutes a dynamic and creative cultural dialogue that has produced distinctive hybrid architectural forms rooted in local identities. This research contributes to the broader scholarship on Islamic architecture while supporting ongoing efforts toward the preservation of Central Asia's rich cultural heritage.